2014
DOI: 10.1017/s1743921315003464
|View full text |Cite
|
Sign up to set email alerts
|

Stellar masses calibrated with micro-lensed quasars

Abstract: Abstract. We measure the stellar mass surface densities of early type galaxies by observing the micro-lensing of macro-lensed quasars caused by individual stars, including stellar remnants, brown dwarfs and red dwarfs too faint to produce photometric or spectroscopic signatures. Our method measures the graininess of the gravitational potential, in contrast to methods that decompose a smooth total gravitational potential into two smooth components, one stellar and one dark. We find the median likelihood value f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The magnification of SNe from stars is studied in (53), where it is found that ∼ 70 % of multiple lensed SNe will experience additional magnification from the lens galaxy star population of > 0.5 mag. The case of lensed quasars is studied in, e.g (54).…”
Section: Modelling Of the Gravitational Lensmentioning
confidence: 99%
“…The magnification of SNe from stars is studied in (53), where it is found that ∼ 70 % of multiple lensed SNe will experience additional magnification from the lens galaxy star population of > 0.5 mag. The case of lensed quasars is studied in, e.g (54).…”
Section: Modelling Of the Gravitational Lensmentioning
confidence: 99%
“…Strong gravitational lenses have been used extensively to study the structure and late (z < 1) evolution of massive galaxies, both through the detailed study of a small number of systems (see e.g. Sonnenfeld et al 2012;Barnabè et al 2013;Smith et al 2015;Collett et al 2018;Schuldt et al 2019) and with the statistical combination of tens of objects (Auger et al 2010;Bolton et al 2012;Schechter et al 2014;Oguri et al 2014;Sonnenfeld et al 2015;Oldham & Auger 2018). However, strong lenses are rare systems, and dedicated follow-up observations are usually required to confirm their nature and to obtain all of the necessary information for a successful analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Under that assumption, the problem reduces to the determination of a handful of parameters describing the average of the distribution and possible scaling relations between the mass parameters of each lens and some galaxy properties (see, e.g. Rusin & Kochanek 2005;Grillo 2012;Oguri et al 2014;Schechter et al 2014). A more general method for inferring the statistical properties of an ensemble of lenses is hierarchical modelling, in which lenses are still assumed to be drawn from a common distribution to be inferred from the data, but where the parameters describing individual objects are allowed to vary independently of each other (see Sonnenfeld et al 2015Sonnenfeld et al , 2019aBirrer et al 2020;Shajib et al 2021).…”
Section: Introductionmentioning
confidence: 99%